A necessidade de afiliação: um levantamento crítico - Leite, Elisameli Paiva de Vilhena (1978)
This dissertation has pretended to do a critical survey about researches made regarding need affiliation. Arising from general explanations, based on learning and-instinct concepts it was approached to news and specifics assessments which put out, mainly, personality and affective orders variables in the growth of affiliative behavior. It was designate the features of this assessments that may be considered ambiguous or contradictories reaching to enclose methodological, conceptual and theoretical questions. It was tried, finally -purposing cooperate for a extension of researches related with this type of motivation suggest a relation between need of affiliation and some variables considered in the study of interpersonal attraction. The achievement of this research constitutes a future project of the author.